(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
The importance of extension projects for teacher training is noticeable, as well as the social relevance of actions aimed at education and scientific dissemination. Thus, we seek to discuss how extension projects of the Institute of Biology at Universidade de Brasília (UnB) contribute to education and scientific dissemination through the analysis of the activities developed. The methodology consists of document analysis of extension projects, in addition to questionnaires aimed at coordinators and extension workers. The found results demonstrate how the curricularization of extension actions is seen as an opportunity to increase participation at UnB, but it requires incentives, bureaucratic improvements, financial support, greater faculty involvement, and the need for guidance in student education. Furthermore, it emphasizes the importance of creating and maintaining extension initiatives focused on scientific dissemination, with methods of analysis and evaluation to enhance these actions.